Attitude Formation Towards Local and International Ecological Face and Body Care Brands Among Lithuanian Female Consumers - Pikturnienė, Indrė; Mackelaitė, Aistė (Organizations and Markets in Emerging Economies, 2013)
Current environmental trends in production and marketing resulted in a close-loop situation, when on the one hand consumers demand environmentally friendly and ecological products and are ready to pay price premiums for them, on the other hand, marketers explore usage of environmentally friendly brands and labels as a competitive advantage. Both local and international brands compete in the market of ecological products. However, consumer propensity to purchase ecological brands differs, as this variable can be a function of a number of factors. The paper analyses the impact of consumer values, perceived environmental knowledge and pro-environmental concern on consumer attitudes towards ecological brands (local or international), and the influence of consumer attitude elements on intention to purchase local vs. foreign ecological brands in the industry of face and body care. Lithuanian women were polled to determine the relationship of these variables. The results indicate that the attitude towards an ecological product is related to the value of a sense of belonging and pro-environmental concern; intention to purchase a local brand is predicted by the attitude towards the local brand only, whereas intention to purchase an international brand is predicted by the attitude towards an international and ecological brand, and negatively correlates with the attitude towards a local brand.
Keywords: attitude towards an ecological brand; pro-environmental concern; perceived environmental knowledge; local vs. international brand; theory of Planned Behavior